Evaluasi Ketepatan Obat Antidiabetik Dan Antihipertensi Pada Pasien Diabetes Mellitus Tipe 2 Dengan Komplikasi Nefropati Di RSUD Dr. Moewardi Surakarta Januari-Juli 2014 - Falah, Elit Rizal (2016)
Diabetic nephropathy is considered a kind of severe complication of diabetes mellitus and lead to a major cause of terminal renal failure. The prevalence of this complication gradually increases each year. This study was aimed at to find out the appropriatness of the drugs used for thediabetes patients with nephropathy complications at RSUD Dr. Moewardi Surakarta in January to July 2014. This study is considered as a non-experimental descriptive study with retrospective data collection. The sample of this study was taken from the medical records of the type 2 diabetes mellitus patient with the complications of nephropathy at Dr. Moewardi hospital who met the inclusion criteria. The inclusion criteria included in this study are the patient who suffer from nephropathy complication, 45 years old, having complete medical record, and the diabetes patient with nephropathy who characterized by persisten proteinuria at one or two times check up with creatinine of more than 2,5 mg/dl. The results obtained from the appropriatness of antidiabetic drug given to patients were 100,00% for the right indications, 98.31% for the right drugand 86.44% for the rightpatient. Meanwhile, the results obtained from the use of antihypertensive were 100,00% for the right indications, 92,59% for the right drug, 96,00% for the right patient and 88,00% for the right dose.